The dynamics of play – back to the basics of playing. Issue 1 (2nd January 2017) - Holst, Jonas
ABSTRACT: In his seminal work Homo ludens the Dutch historian Johan Huizinga laid out the pieces for a theory of play rooted in anthropological and cultural analysis, but he did not gather the pieces into a systematic account of the dynamics of play. Starting out from Huizinga's observations of a common pattern in how play is designated and expressed in different languages, the paper argues that we need a deeper phenomenological analysis of what goes on at the most basic level of playing in order to draw out the specific characteristics of play. The paper bases its phenomenological analysis on Hans-Georg Gadamer's condensed reflection on play as an on-going, alternating movement to-and-fro, observable in many kinds of play, and it proposes to tap deeper into the dynamics of play with the aim of offering a systematic investigation of little-explored facets of playing, primarily displaying, testing and risking.